Dydaktyczne aspekty powieści dla dziewcząt na przykładzie wybranych utworów Marty Fox - Świercz, Katarzyna (Dydaktyka Polonistyczna, 2019)
Literary works dedicated to adolescent girls are primarily aimed at preparing young readers for the roles that await them in adulthood. The type of didacticism chosen by authors of this type of prose has been evolving along with the history of the subgenre and transformations in the field of pedagogy. The direct, narrative moralizing of the young reader gave way to the place of presentation of educational assumptions that are introduced to the books by constructing the fates of heroes, allowing readers to draw their conclusions and assessments independently. The prose for the youth by Marta Fox refers to the historical determinants of the novel for girls and didactic traditions of this genre. The author, however, avoids direct instructions, at the same time remembering about the educational message while constructing various elements of the presented world.